Analysis of the rectifying separation of H2O–D2O mixture into light and heavy water by means of mathematical modeling - T. G. Korotkova; G. I. Kasyanov (Тонкие химические технологии, 2022)
Objectives. To apply an analytical method for the calculation of a distillation column for the production of D2O at a two-column Kuhn installation operating under vacuum: to simulate the Kuhn installation in the Hysys software; and to compare experimental and calculated data.Methods. Analytical method for the calculation of distillation columns “from stage to stage,” from the lower theoretical separation stage (TSS) to the upper stage. This method is based on phase equilibrium at the TSS with known data of input flows and component concentrations in the column bottoms. Hysys was used as modeling software.Results. Comparison of the calculation results with Kuhn’s experimental data testified to the high calculation accuracy of the vapor–liquid phase equilibrium for the H2O–D2O mixture at the TSS. The convergence of the D2O material balance for the entire installation was 0.005%. The identification parameter was the number of the column feed plate. Simulation of the Kuhn installation in the Hysys software showed a qualitative agreement of D2O concentrations in material flows. The UNIQUAC (UNIversal QUAsiChemical) model was used to calculate activity coefficients. The found values of the number of theoretical separation stages (NTSS) in both columns, were 88 and 153 taking into account the reboiler and condenser. This is less than the experimental 295 and 400, respectively. The discrepancy can be explained by the increased phase equilibrium H2O constant in the UNIQUAC model. However, the convergence of the material balance in terms of D2O was high and amounted to 1.38·10−6 %. The absolute error of the found concentrations in material flows did not exceed 0.12 mol %.Conclusions. The results obtained indicated the possible use of the Hysys modeling software when searching for and optimizing the operating mode of the block diagram of a cascade of distillation columns with direct and recycle flows to separate a mixture of water into light and heavy water. The final results obtained with regard to the operating mode, inlet and outlet material flows (flow rate, composition, temperature, and pressure drop across the column) are recommended for use in the analytical program for the calculation of the distillation column to refine the NTSS and distribution profile of the concentrations of the H2O and D2O components along the height of the column.